Predictors of midwifery graduate outcomes in Palestine: a cross-sectional study of curriculum quality, faculty support, and regional disparities - Ibrahim Aqtam; Mustafa Shouli; Saja Aydi; Maysam Morar; Lana Abu Arrah; Amena Abu Rayan (BMC Nursing)
Abstract Background Midwifery education critically shapes graduates’ employment status and satisfaction. This study identifies predictors of employment outcomes and satisfaction among Palestinian midwifery graduates, focusing on sociodemographic factors, curriculum quality, clinical training, and faculty support. It also analyzes regional employment disparities and satisfaction variations across graduation cohorts. Methods 273 graduates of the Midwifery Bachelor’s Program at Ibn Sina College of Health Professions completed a cross-sectional survey. Data collected included sociodemographic information, employment status, and satisfaction with curriculum, clinical training, and faculty support. Instrument validity was confirmed with a Content Validity Index (CVI) of 0.84. A pilot study (n = 27) refined the survey. Statistical analyses included Chi-square tests, Pearson’s correlations, and multiple logistic regression, with results presented as odds ratios (OR) and 95% confidence intervals (CI). Results Graduates under 25 years had lower employment rates (OR = 0.68, 95% CI: 0.50–0.92, p = 0.036), while married graduates were more likely to be employed. Strong faculty mentorship tripled employment odds (OR = 2.75, 95% CI: 1.81–4.18, p = 0.002). Curriculum quality moderately correlated with satisfaction (ρ = 0.32, p = 0.001). Neonatal training satisfaction was lower (33% excellent, 55% good), with identified gaps in clinical preparedness. Employment disparities across regions were statistically significant (χ² = 10.82, p = 0.001), favoring the northern West Bank. Conclusion Improvements are needed in neonatal care training and faculty mentorship. Clinical rotations in high-risk settings should expand. Future research must include socioeconomic status and prior healthcare experience as variables. Regional job placement initiatives are necessary to address employment disparities. Clinical trial number Not applicable.